Un exemple de charpente à double croupe du début du xiiie s. : la porterie du prieuré de Courtozé à Azé (Loir-et-Cher) - Franck Tournadre (Revue Archéologique du Centre de la France)
Located in an isolated valley near Vendôme, the former priory of Courtozé in Azé (Loir-et-Cher) preserves a medieval building that was once the gatehouse, associated with fragments of an enclosure wall. In addition to the great architectural interest of the building, whose construction methods fit perfectly into the productions of the Grand Ouest of France, especially in elite housing, it still has a rare double-hip roof structure, synchronous with the masonry. A building study and a campaign of dendrochronological analyses have revealed a unique ensemble from the early 13th century, never documented before. The unique arrangements of the roof structure, originally equipped with bracing with ridge and sub-ridge, reveal a sophisticated technical design. The uncommon organization of this rural establishment in the Middle Ages also prompts us to question the functions of this dependency of the Abbey of the Trinity of Vendôme.